Le régime du caoutchouc : esclavage et travail forcé. Le Congo de Léopold II, 1885-1908 - Loffman, Reuben (Les mondes de l'esclavage: une histoire comparée, 2021)
Keywords: Tippo Tip (1837-1905)

Mémoires de l'émancipation : côte kényane, XIXe-XXe siècles - Abungu, Patrick; Ballarin, Marie Pierre; Nyanchoge, Samuel (Les mondes de l'esclavage: une histoire comparée, 2021)
Keywords: Esclavage – Zanzibar

Narrative Techniques and Aims of the Discourse on Military Expeditions and Coastal Defense in Ramon Muntaner’s "Crònica" (1328) - Orazi, Veronica (Approaches to New Trends in Research on Catalan: Studies Linguistics, Literature, Education and Cultural Studies, 2021)
Ramon Muntaner was not a professional writer and composed only one work. He was rather a captain, a diplomat, a governor, a man very close to the Crown. His personal experience of war is witnessed in his Chronicle, according to two different narrative mechanisms: the technologization and the literarization of the described events. The defense during the Crusade against the Crown of Aragon (1283-1285) concretizes the author’s peculiar dichotomy technologization-literarization of history, emphasizes a perfect military strategy and the final victory; the narration of expansion through the Mediterranean is developed both in the conquest of Djerba and the Kerkennah Islands (1309-1314) and in the campaign of Sardinia and Corsica (1323-1324), but from two different points of view: the former offers an exemple of self celebration, which is possible because of its relative relevance if compared with other epochal events related in work; the latter is based on the documentation that the admiral Carrós sent to the King, as Muntaner did not participate in it. Finally, the expedition of the Catalan Company to the East (1303-1308) synthetises all these features and represents one of the highest moments of the whole Crònica.
Keywords: Invasions chrétiennes – Djerba; Muntaner; Ramón (1265-1336)

الدور الاجتماعي والسياسي للمجالس العامة (السَّبْل) في نزوى (2012-1913م) - الخروصي, عبد العزيز بن هلال (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

مظاهر الحياة الاقتصادية في مدينة نزوى، المزاد العلني أنموذجاً - الخروصي, محمد بن جمعة (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

الحياة الاقتصادية في ولاية نزوى في منتصف القرن العشرين - الهنائي, سليم بن محمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

ملامح التعايش السلمي من خلال جوابات فقهاء مدينة نزوى في عهد اليعاربة - السعدي, ناصر بن سيف (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

الدور الحضاري للأوقاف والأفلاج في ولاية نزوى - البوسعيدي, موسى بن خميس بن محمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

الأزياء وأدوات الزينة في المجتمع النزوي خلال القرن (10-2ه/ 16-8م) - الشعيبية, بدرية بنت علي (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

الأرض والزراعة في عُمان من خلال كتاب المصنف للشيخ أحمد بن عبد الله الكندي النزوي (ت: 557ه/1162م) - القدحات, محمد بن عبد الله (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)
Keywords: Agriculture – Oman

ملامح من الألقاب السياسية في دولة الإمامة في عُمان خلال القرن 14ه/ 20م، دراسة وثائقية - الجوهرية, أحلم بنت حمود (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

العمارة الحربية في مدينة نزوى التاريخية، قلعة نزوى نموذجًا - المعمري, هيفاء بنت أحمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

نزوى في الوثائق البريطانية، دراسة لحقبة الخمسينيات من القرن العشرين - شلبي, عبد الحميد عبد الجليل (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

أبرز مظاهر العلاقة بين نزوى ومسقط خلال الفترة (1378-1331ه/ 1959-1913م) - المحذوري, عبد العزيز بن حميد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

الأهمية السياسية والفكرية لنزوى في النصف الثاني من القرن الثامن عشر الميلادي - الخروصي, صالح بن عامر (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

مراسلات العلماء حول تنصيب سلطان ابن سيف بن سلطان اليعربي بالإمامة (1131-1123ه/ 1719-1711م) - الهاشمي, سعيد بن محمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

مكانة نزوى التاريخية في عهد دولة اليعاربة، دراسة في أحوالها السياسية والاقتصادية والاجتماعية - عبد الغني, مجدي رشاد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

الأسر العلمية النزوانية في القرن 3ه/9م، دورهم الثقافي ومواقفهم السياسية - سلامة, إبراهيم عبد المنعم (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

نزوى عاصمة لعُمان في عام 177ه/794م، المؤهلات والدوافع والنتائج - المنذري, محمد بن ناصر (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

علاقة عُمان بالخلافة العباسية (280-134ه/ 893-751م)، المسلّمات والإشكاليات - الوهيبي, خالد بن خلفان (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

أئمة نزوى في تاريخ عُمان - التميمي, حميد أحمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

مدينة نزوى، دراسة في أحوالها الحضارية قبل الإسلام - كاظم, شاكر مجيد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

الدور الحضاري لنزوى منذ أقدم العصور حتى قبيل الإسلام - السعيد, عصام محمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

نزوى في شعر المناسبات الوطنية (2015-1970م) - الصباري, خميس بن ماجد بن خميس (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

حضورُ نزوى وعُمان في وجدان الشعراء الجزائريين منذ حوالي 250 سنة إلى العصر الحديث - جهلان, محمد بن أحمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

القيم التربوية في الحكايات الشعبية العُمانية، الحكاية الشعبية النزوية أنموذجاً - أمبوسعيدي, عبد الله بن خميس; العامري, محمد بن حمود; الجامعية, أمل بنت عبد الله; الحوسنية, هدى بنت علي (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)
Keywords: Littérature – Oman

الصلات الثقافية بين علماء نزوى وبلاد المغرب في مجال التأليف خلال القرنين 13 و14ه/ 19 و20م - فخار, جابر بن سليمان (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

التواصل الحضاري بين عُمان وبلاد المغرب في العصر الحديث، زيارات الوفود نموذجاً - الصقري, سعيد بن عبد الله (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

صورة نزوى في فكر الإمام السالمي، تحفة الأعيان بسيرة أهل عُمان أنموذجاً - النبهاني, سعود بن سليمان (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

حديث الإنصات، دراسة في مجلس المُفَضّلي النزوي وابن رزيق - السعيدي, أحمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

ديوان أنوار الأسرار ومنار الأفكار وموضوعاته وخصائصه الفنية لناظمه عامر بن علي بن مسعود العبادي النزوي - الحسيني, راشد بن حمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

السيرة العبادية، قراءة وصفية تحليلية - الخروصي, أحمد بن سالم (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

الحياة الفكرية بنزوى في عهد دولة اليعاربة (1157-1034ه/ 1744-1624م) - الخضوري, طالب بن سيف (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

محمد بن مدَّاد وقصيدته المرتدَّة، تحقيق وتعليق - شريفي, مصطفى بن محمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

إسهام المساجد والأبنية الأثرية بمدينة نزوى في ازدهار ونشر الحركة العلمية والدينية في عُمان وشرق أفريقيا - كامي, أبو ياسر مبورعلي (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

المؤسسات التعليمية (الكتاتيب، المساجد، المجالس العلمية) ونظام التعليم فيها - البطراني, جمعة بن خلفان (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

ملامح التفسير اللغوي عند الإمام جابر بن زيد - أبو ستة, إيهاب محمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

الصلات الثقافية والفكرية لنزوى مع البصرة وبلاد المغرب وحضرموت - أمبوسعيدي, عبد الله بن سعود (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

المدرسة الفقهية النزوية - الكندي, أحمد بن يحيى بن أحمد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

التبادل الثقافي بين بيضة الإسلام والبصرة في القرون الأولى للهجرة - كامل, محمد سيد (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)

Le géomorphosite culturel de Matmata (sud-est tunisien): paysage et habitats troglodytiques - Boukhchim, Nouri (Povoações alcandoradas: arquitectura e paisagem : 2o Congresso Internacional Arquitectura tradicional no Mediterrâneo ocidental = Villages perchés : architecture et paysage : 2ème Congrès International Architecture traditionnelle en Méditerranée occidentale, 2021)
OCLC: 1284805807
Keywords: Architecture – Matmata; Urbanisme – Matmata

They Never Thought a Yankee Could Do So’: Sayyid Saʿid bin Sultan and the Anglo-American Rivalry in the Indian Ocean - Roberts, Nicholas P. (Oceanic Circularities: Mobile People and Connected Places in the Indian Ocean, 2021)

شكان وأسواق دَبَا فرضة عُمان والعرب المشهورة في عصري الجاهلية وصدر الإسلام - أبو العلا, إبراهيم عبد المنعم (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

شذرات من تاريخ مسندم خلال فترة اليعاربة (1749/1162 - 1624/1034) - البراشدي, موسى بن سالم (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

مسندم رأس ماكيتا ماكا/ مجان) والشحوح في المصادر القديمة: الكتابات المسمارية، التوراة، المصادر اليونانية والرومانية، النقوش الفارسية والمسند اليمني - الجرو, أسمهان سعيد (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

مفردات من الماضي حول الحياة العُمانية في محافظة مسندم وادي مدحاء نموذجاً - السعدي, عبد الله بن علي (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Vie intellectuelle – Oman

مدخل للموضوعات التي تناولتها أوراق العمل - الضوياني, حمد بن محمد بن ضويحي بن خلفان; الجهورية, أحلام بنت حمود (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

النشاط التجاري البحري في محافظة مسندم التجارة البينية - الغيلاني, حمود بن حمد (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

صورة مسندم فى كتابات الرحالة الغربيين خلال القرنين 19 و20 الميلاديين - المحذوري, سلیمان بن عمير (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

تاريخ مسندم في العهد النبوي والخلافة الراشدة - المنذري, محمد بن ناصر (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

علاقة مسندم السياسية بساحل عُمان الشمالي ومنطقة الشميلية - الهاشمي, سعيد بن محمد (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

البعد الجغرافي والسياسي لإقليم مسندم - الهنائي, سليم بن محمد (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

الخصائص الاجتماعية والاقتصادية ومستويات التنمية البشرية لسكان محافظة مسندم - عبد الغني, منتصر إبراهيم (مسندم في ذاكرة التاريخ العماني, 2021)
Keywords: Musandam (Oman) – Histoire

Notices relatives à l'État indépendant du Congo et projets antérieurs ([1876-1884] 1885-1908) - Tallier, Pierre-Alain; Van Eeckenrode, Marie; Van Schuylenbergh, Patricia (Belgique, Congo, Rwanda et Burundi : Guide des sources de l'histoire de la colonisation (19e-20e siècle), 2021)
Keywords: Archives – Bruxelles; Esclavage – Oman; Esclavage – Zanzibar; Relations – Oman – Belgique; Tippo Tip (1837-1905)

Notices relatives à la Belgique et aux territoires sous autorité belge : Congo, Ruanda Et Urundi ([1884]1909-1960/1962) - Tallier, Pierre-Alain; Van Eeckenrode, Marie; Van Schuylenbergh, Patricia (Belgique, Congo, Rwanda et Burundi : Guide des sources de l'histoire de la colonisation (19e-20e siècle), 2021)
Keywords: Archives – Bruxelles; Esclavage – Oman; Esclavage – Zanzibar; Relations – Oman – Belgique; Tippo Tip (1837-1905)

Notices relatives aux territoires africains sous autorité allemande : Afrique Orientale Allemande (1890-1916) / Notices relatives aux archives d'origine allemande produites dans le cadre de l'occupation de la Belgique durant la Deuxième Guerre mondiale et concernant des sociétés belges actives au Congo et au Ruanda-Urundi - Tallier, Pierre-Alain; Van Eeckenrode, Marie; Van Schuylenbergh, Patricia (Belgique, Congo, Rwanda et Burundi : Guide des sources de l'histoire de la colonisation (19e-20e siècle), 2021)
Keywords: Archives – Bruxelles; Esclavage – Oman; Relations – Oman – Belgique; Tippo Tip (1837-1905)

La communauté djerbienne installe au grand Tunis : la dimension sociale du mouvement de ses femmes - Bassalah, Safa (Migrations méditerranéennes du Moyen Âge à nos jours: institutions et liens sociaux, 2021)
Keywords: Emigration – Djerba – Tunis

Husn al-Baleed, a mediaeval fortified castle along the Omani coast: preliminary results from the 2016-2017 excavations - Pavan, Alexia (Contacts between South Arabia and the horn of Africa, from the Bronze age to Islam: in honor of Rémy Audouin, 2021)
Keywords: Archéologie – Oman

Iran's relations with Bahrain, Oman, and the United Arab Emirates - Güney, Nurşin Ateşoğlu; Keynoush, Banafsheh; Korkmaz, Vişne (Iran’s Interregional Dynamics in the Near East, 2021)
Few regions in the world are as torn by conflicts as the Near East, in which Iran plays a central role. Opportunities to engage with Iran are abundant, ...
Keywords: Relations – Oman – Iran

La question d'un consensus patrimonial autour de la vision polysémique de la notion de patrimoine à Djerba - Bielawski, Mathilde (Patrimoine, langue, discours et tourisme, 2021)
Keywords: Monuments – conservation – Djerba

تحبيس الفندق المعروف سابقا بالبيطاري بسوق جربة الكبير على مدرسة قابس سنة 1104هـ/1693م - بربو, المنصف (Patrimoine, langue, discours et tourisme, 2021)

Les bêtes sauvages et la chasse en Ifrîqiya au Moyen Âge - Hassen, Mohamed (L’Homme et l’Animal au Maghreb, de la Préhistoire au Moyen Âge : Explorations d’une relation complexe, 2021)
Being one of the natural qualities of man, hunting is thought differently depending on whether it is the prince to the commoner. This theme will be addressed in three areas :– the hunter ;– types of prey : wild animals, which are not always harmful, are very varied : wild animals (lion, tiger, wolf), sweet beasts (herbivores, biting, claw animals, reptiles) ;– hunting methods and techniques : equipment, animal hunting, cunning.So what is the place of hunting in the Ifrîqiyan society in the Middle Ages and its effect on flora and fauna ?,Étant une des qualités naturelles de l’homme, la chasse est pensée différemment selon s’il s’agit du prince ou du roturier. Ce thème sera traité en trois axes :– le chasseur ;– les types de proie : les animaux sauvages, qui ne sont pas toujours nuisibles, sont très variés : bêtes fauves (lion, tigre, loup), bêtes douces (herbivores, mordants, animaux à griffes, reptiles) ;– les méthodes et les techniques de chasse : les équipements, la chasse aux animaux, la ruse.Quelle est donc la place de la chasse dans la société ifrîqiyenne au Moyen Âge et son effet sur la faune et la flore ?

The Road to Ghardaïa: Investigating a Community Deep in the Sahara Leads to the Study of Global History - Holsinger, Donald C. (Mennonites and Post-Colonial African Studies, 2021)
Keywords: Emigration – Mzab – Algérie

محاولة في قراءة جديدة لطبيعة العلاقات بين الأدارسة وبني رستم بناء على أخبار نادرة للرازي صاحب أخبار فخ - النوري, نور الدين (السكان والمجال والسلطة في العالم الإسلامي. كتاب جماعي تكريما للأستذ إبراهيم جدلة, 2021)
Keywords: Relations – Rustumides – Idrissides

The Ibāḍī: al-Wārjalānī - Husayn, Nebil (Opposing the Imam: The Legacy of the Nawasib in Islamic Literature, 2021)
Chapter 4 discusses the literary heritage of one of the least discussed sects in Islamic history, Ibāḍism. The Ibāḍīs portray ʿAlī as having been a righteous Muslim and a legitimate caliph until the end of the battle of Ṣiffīn. At that point, they believe, he took an ignoble turn to misguidance in his quest for power. This image of ʿAlī differs from ʿUthmānī and Umayyad portrayals of him as vicious and sinful throughout his life. This chapter draws primarily on the Kitāb al-Dalīl of Abū Yaʿqūb al-Wārjalānī (d. 570/1175), an influential Ibāḍī scholar, complemented by expressions of anti-ʿAlid views in other authoritative Ibāḍī historical works. These texts demonstrate that the Khārijī legacy of anti-ʿAlidism survives even in the contemporary world.

Adaption and Autonomy in the Architecture of Roman North Africa. The Basilica of Meninx, a Case Study - Stoeßel, Linda (The Basilica in Roman Palestine: adoption and adaption processes, in light of Comparanda in Italy and North Africa: workshop, 5-6 December 2019, Tübingen, 2021)
Keywords: Archéologie – Djerba

Arab Merchants in Middle Period China - Chaffee, John W. (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)
Keywords: Relations – Oman – Chine

Cross-Boundary Knowledge in Early Ibāḍism: Exchanges, Religious Authority and Knowledge Transmission - Francesca, Ersilia (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Exploring Discursive Networks: The Case of “Adhering to the Community” (Luzūm al-Jamāʿa) Narrations Among Early Ibāḍīs - Gaiser, Adam R. (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Transmission of Ibāḍī Knowledge: Between China and Oman - Ghazal, Amal N. (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

What Is the Purpose of the Chinese Phoenix in Oman’s Mosques? - Hajri, Hilal al- (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)
Keywords: Architecture – Oman

A Personal Narrative of a Maghribī-Ibāḍī Religious Lineage - Jaabiri, Farhat (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Chinese Porcelains Embedded in Omani Miḥrābs. International Trade and Cultural Relations - Karakitsos, Stratos (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)
Keywords: Arts – Oman

Rāshid b. ʿUmayra l-Rustāqī and Medical Treatment in 16th-Century Oman - Kondo, Yohei (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

The Sohar Ship: Cultural Symbol and Spiritual Impetus for the Belt and Road Initiative - Lin, Luo (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

The Cultural Interactions between the Middle East and Japan through the Silk Road - Morimoto, Seiji (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Retracing Qatāda’s al-Nāsikh wa-l-Mansūkh in Early Ibāḍī Sources - Muranyi, Miklos (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Letter of Marque: The Gwadar Enclave of Ibāḍī Sultans of Oman and Its Interconnections with Asia - Nicolini, Beatrice (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

The Silk Route, a Tenuous Whirling Line Between Past and Present: The Manṣūra Emirate and Its Outlet to the Sea, Daybul (9th–10th Centuries) - Piacentini Fiorani, Valeria (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Hermes Depicted by Scythians or Sakas - Qing, Duan (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Regulating Seafaring in Early Islamic Jurisprudence: A 3rd/9th Century Ibāḍī Manuscript on Maritime Law - Salimi, Abdulrahman al- (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Silk Road of Japan via China in the 7th Century and the Concepts of Grace, Islam, and Ibāḍī Muslims in a Structural Analysis of the Teaching of Islam - Shinohe, Junya (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Intersections within Arabic and Chinese Navigational Literature: Star-Altitude Measurements - Staples, Eric (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)
Keywords: Navigation – Oman

Early Oman and China Relations Studies - Xiaofu, Wang (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

On the Islamic Sects in China - Yujie, Wang (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

Epilogue - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
International negotiations based on pure national interest cannot provide sustainable models for treaty-making when global issues, like nuclear weapons or climate change, are at stake. The Iran nuclear deal is a case in point as it was easily set aside by the Trump administration. Increasing risks of the deal failing and its likely consequences, proliferation of nuclear weapons and regional conflict, are bound to have negative repercussions for other treaty regimes hanging on a thread, like the Treaty on the Non-Proliferation of Nuclear Weapons. National interest is not an intelligent model for international treaty making in this context. Like in the falaj microcosms, the genuine accommodation of the interests of everyone is likely to produce durable outcomes. Serious engagement by all parties to the negotiation as well as reconciliation of past animosities are also necessary requirements for successful negotiation. The role of skilful mediators, drawing from best customary practices, becomes a requisite throughout the negotiation process.

Falaj and Agreement - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
Omani irrigation channel (qanat falaj) construction is very old. The identity of the original qanat builders is still debated by the research community. An Omani legend ties the existence of specific daudi falaj to the times of King Solomon of the Old Testament. Persian Achaemenid Shahs and Sasanian Shahs actively encouraged channel construction in the region. Whomever the original builders were, these systems have provided communities in the northern Omani interior with water for irrigation and domestic use for at least 1500–2000 years. Villages form microcosms in which a falaj organization has a clear social and economic structure, based on an accurate and fair system of water distribution. Over 3000 falaj are still very much in use, providing over one third of irrigation water today. Unlike meticulous regulation in Persia proper, Omani irrigation law was devoid of unnecessary legislation. Customary principles and Islamic law were consolidated into a harmonious whole. This was accomplished the Islamic legal scholars, the ulama. Fair dealing, consultation and collective responsibility created relative harmony at the level of the villages. Most disputes, if any, were settled in consultation with falaj officials, wakil and arif.
Keywords: Droit maritime – Oman

Historical Landscapes - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
Omani civilization is very old. Early Bronze Age civilization in the fourth millennium BC unified the whole Oman peninsula from the Abu Dhabi islands to Ra’s al-Hadd and Masirah Island. Coastal regions were in constant touch with the outside world as boats, loaded with copper, diorite and frankincense travelled far, from the south-eastern shores of Africa along the coast of the Indian Ocean rim. In contrast, villages in the Hajar mountains formed isolated pockets in the valleys and on the slopes of the mountains. Regardless, the irrigation was a matter for the village where agreements over irrigation systems were negotiated and managed on a customary basis. The governing power, whether it was a religious Imam, a secular king, a sultan or a foreign occupier, was a factor in the village reality. At times this was beneficial, as under the First unitary Imamate in the eighth to ninth century, when customary law and Islamic law on irrigation were consolidated into a harmonised whole. At times, the collapse of central power and subsequent internal fighting between the tribes resulted in significant destruction and the abandonment of settlement. The birth of a modern Omani state in the latter half of the twentieth century under Sultan Qaboos signalled a break with the past, except for the culture, which continues to live in the traditions and laws of the people of the land.
Keywords: Oman – Histoire

Ibadi Islam and the Imamate Tradition - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
The roots of Ibadism can be traced back to the times of the fourth and last of the rightly guided Caliphs, Ali Abi bin Talib. Two important secessions took place from the mainstream Sunni Islam during Ali’s time: that of the Shia and that of the Kharijite, a loose grouping of different sections from which also the Ibadis would emerge later on. Oman and North Africa became strongholds for the developing Ibadi school of thought. The North African Ibadi Rustamid Imamate lasted until 296 AH/909 AD when it was overthrown by the Shiite Fatimids. Since then, the Ibadi African communities formed isolated pockets in Algeria, Libya and Tunisia but were never able to establish an Ibadi imamate again. In Oman, matters were different as Ibadism became the unifying factor for the tribes. Later came the wars of independence from the central Caliphate with the establishment of Ibadi Imamates. Imamate governance signified the imposition of rule of law—like conditions in the country, after years of unchecked tribal rule. The Ibadi Imamate was a supra tribal state, in that its legitimacy and power derived directly from tribal support. Islamic governance was based on law, starting with the choice of the Imam by consultation. Islamic legal scholars, the ulama, and the Imamate officials would influence the Omani cultural landscape, encouraging consultation and fairness in the conduct of everyday affairs.
Keywords: Droit maritime – Oman

Introduction - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
Negotiations that produce durable outcomes are rather rare in international negotiations, which are often viewed as a zero-sum game in which one’s success is tied to the other’s loss. The Iran nuclear deal, negotiated in 2015, is a case in point. The original deal was the product of unbalanced negotiations. The deal’s compliance pull resulted weak, making it relatively easy for President Donald Trump to pull the US out of the deal in 2018. The search for more constructive ways of negotiation led to the path that became this book. An example of inclusive negotiations that produce durable outcomes was found in Oman, a historical seafaring nation, situated on the southeast corner of the Arabian peninsula and bordered by the Arabian Sea and the Indian Ocean. In Oman, water is the lifeblood of all life. Inclusive agreements over irrigation channels developed into Omani culture over a considerable time span from custom, Ibadi Islamic principles and tribal law. The Omanis became known as the people of consultation, Ahl Al-Shura.
Keywords: Droit maritime – Oman

Oman Water Diplomacy Part I: The Beginnings of the Middle East Desalination Research Centre (MEDRC) - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
Omani water diplomacy has its roots in the cultural landscape of the Omani society. Omani falaj communities formed microcosms in which principles of consultation, mediation and fairness developed over centuries into an internalized code of conduct whose influence would later extend also to the conduct on the nation’s foreing policy. Sultan Qaboos’ rise into power in 1970 signalled a significant break with the isolationist past. From then on, Omani foreign policies departed from dialogue, moderation and inclusion. With these cultural and political resources in the diplomacy toolkit, Oman was ready to take an active role at the Water Resources Working Group of the Middle East Peace Process. Omanis were well-placed to understand the implications of sufficient water supply for regional security. The desalination of sea water was considered to be the key for desert countries in the Middle East for finding new sources of supply of drinking water. The sharing of scientific and technological expertise became the goal of a small group of Omani water architects. A common effort, an international research centre on water desalination based in Muscat was beginning to take shape in the heated climate of international politics around the Arab-Israeli conflict.
Keywords: Droit maritime – Oman

Oman Water Diplomacy Part I: The Establishment of the Middle East Desalination Research Centre (MEDRC) - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
In the volatile context of the Middle East Peace Process, financial independence of the Research Centre was a necessity. It would mean independence to decide on research, training and technical requirements on the basis of project appropriateness alone. Resilience, extra miles and diplomatic tact were required from the water architects to secure the sound funding of the Centre. The Centre was going to be based on grass-root cooperation between experts of different countries, including Israel, solidly committed to making the Centre a reality. Through benefits of participation, common ground was prepared for the betterment of Arab-Israeli—relationships. The Establishment Agreement of the Middle East Desalination Research Centre was signed in Muscat in 1996 by the founding members, Oman, the US, Japan, Israel, South Korea and the EU. Others would join later on to carry out important research cooperation on water desalination technologies. MEDRC became an independent international organisation under Omani law and a forum for research cooperation for purposes of solving the common problem of water scarcity. Lessons learnt of the MEDRC have potential wider applicability for creating professional grass-root cooperation in the region.
Keywords: Politique étrangère – Oman

Tribalism and Local Agreement - Simonen, Katariina (Ancient Water Agreements, Tribal Law and Ibadism: Sources of Inspiration for the Middle East Desalination Research Centre – and Beyond?, 2021)
Omani society is fundamentally a tribal mosaic. The main tribal confederations since the eighteenth century civil war are the Hinawi and the Ghafiri. The patchwork of Omani tribes belongs to one of these confederations. Omani villages have conserved their tribal outlook, tribal values and tribal structure even if they form sedentarised units instead of a bedu nomadic lifestyle. Tribal alliances between tribes and tribal formation/deformation within tribes has been a continuous process. Tribal law has played an inherent part in the overall formation of Omani legal culture. Central for tribal law are its tendencies towards mediation and the avoidance of conflict. Tribes are egalitarian yet the collective interest is the foundation of tribal law. Every conflict is resolved through arbitration, negotiation or mediation by a third party. All members of the community are expected to do their part in resolving disputes, by restraining people from using force, participating in the mediation process or sharing the costs and the benefits of restitution. The mediation system is sophisticated and highly structured, and it involves a great deal of deliberate negotiation and dialogue to ensure that conflicting parties are content with the resolution. The dispute-resolution system relies on compromise and mutual benefit, rather than on imposed punishment or designation of losers and winners. Collective responsibility implies that tribes are ultimately responsible for the acts of their members and for forcing them to implement verdicts of mediation or arbitration.

La documentation de la production orale des régions berbérophones de Libye (XIXe et XXe siècles) : le Djebel Nefoussa - Di Tolla, Anna Maria (Les études berbères à l'ère de l'institutionnalisation de tamaziyt: mélanges en l'honneur de Salem Chaker et Abdellah Bounfour, 2021)
Keywords: Linguistique – Djebel Nefousa; Vie intellectuelle – Djebel Nefousa

Le mouvement amazigh en Libye sous Kadhafi - Ferkal, Masin (Les études berbères à l'ère de l'institutionnalisation de tamaziyt: mélanges en l'honneur de Salem Chaker et Abdellah Bounfour, 2021)
Keywords: Berbérisme – Libye

Souvenirs des Berbères de Libye - Larcher, Pierre (Les études berbères à l'ère de l'institutionnalisation de tamaziyt: mélanges en l'honneur de Salem Chaker et Abdellah Bounfour, 2021)
Keywords: Vie politique – Djebel Nefousa

L’évolution du discours sur les Berbères dans les sources narratives du Maghreb médiéval (ixe-xive siècle) - Amara, Allaoua (Les berberes entre maghreb et mashreq (viie-xve siecle), 2021)

« Dieu ouvrira une nouvelle porte pour l’islam au Maghreb » Ibn Sallām (iiie/ixe siècle) et les hadiths sur les Berbères, entre Orient et ibadisme maghrébin - Aillet, Cyrille (Les berberes entre maghreb et mashreq (viie-xve siecle), 2021)

Kharijism in the Umayyad Period - Hagemann, Hannah-Lena; Verkinderen, Peter (The Umayyad world, 2021)
"The Umayyad World encompasses archaeology, history, art and architecture, and the study of manuscripts and documents of the Umayyad era (644-750 CE). This era was formative both for world history and for the history of Islam. Subjects covered in detail in this collection include regions conquered in Umayyad times, ethnic and religious identity among the conquerors, political thought and culture, administration and the law, art and architecture, the history of religion, pilgrimage and the Qur'an, and violence and rebellion. Close attention is paid to new methods of analysis and interpretation, including source critical studies of the historiography and inter-disciplinary approaches combining literary sources and material evidence. Scholars of Islamic history, archaeologists and researchers interested in the Umayyad Caliphate, its context and influence on the wider world, will find much to enjoy in this volume"–
Keywords: Kharijisme

Djerba - Latrache, Leila (Généalogie des villes de Tunisie : au carrefour des deux mondes, 2021)
Keywords: Géographie – Djerba

Mascate - Klinger, Thibaut (Abécédaire de la ville au Maghreb et au Moyen-Orient, 2021)
Keywords: Urbanisme – Oman

Religiosity, Men of Learning, and Oil Wealth in the Land of the Imamate - Limbert, Mandana E. (Knowledge, Authority and Change in Islamic Societies, 2021)
Keywords: Moeurs et coutumes – Oman

Aux confins de l'Arabie, la rébellion oubliée du Dhofar - Pellas, Marc; Barthe, Benjamin (Seuil, 2021)
Keywords: Dhofar